The Prevalence of Pediculus humanus capitis and the Coexistence of Intestinal Parasites in Young Children in Boarding Schools in Sivas, Turkey - ÖZÇELİK, SEMRA; DEĞERLİ, SERPİL; MALATYALI, ERDOĞAN; Celiksoz, Ali; Ozcelik, Semra; Mumcuoglu, Kosta Y. (My University, 2012)
The aim of this study was to investigate the prevalence of Pediculus humanus capitis and the coexistence of intestinal parasites in boarding primary schools in Sivas, Turkey. Seven hundred seventy-two students (350 [45.3%] girls, 422 [54.7%] boys) were evaluated with combing for the presence of head lice, collection of fecal samples, and examination of the perianal region for intestinal parasites using the cellophane tape method. The overall infestation rate for head lice was 6% (n = 46). Nine children had evidence of nits only (1.2%), whereas living lice and nits or eggs were found in 37 children (4.8%). Girls were significantly more commonly infested (12.9%) than boys (0.2%). Of the parameters evaluated, socioeconomic level, number of rooms per family, and size and weight of the children were statistically significantly different between the children with and without lice. Although the infestation rate of children with intestinal parasites was higher in the head louse-infested group (23.9%) than in the group of children without lice (17.6%), the differences were not statistically significant.